\(\dfrac{1}{3}.x+\dfrac{2}{5}.\left(x-1\right)=0\)
\(\dfrac{1}{3}.x+\dfrac{2}{5}.x-\dfrac{2}{5}=0\)
\(\left(\dfrac{1}{3}+\dfrac{2}{5}\right).x-\dfrac{2}{5}=0\)
\(\dfrac{11}{15}.x-\dfrac{2}{5}=0\)
\(\dfrac{11}{15}.x=0+\dfrac{2}{5}\)
\(\dfrac{11}{15}.x=\dfrac{2}{5}\)
\(x=\dfrac{2}{5}:\dfrac{11}{15}\)
\(x=\dfrac{2}{5}.\dfrac{15}{11}\)
\(x=\dfrac{6}{11}\)
\(#Siliver\)
\(\dfrac{1}{3}.x+\dfrac{2}{5}.\left(x-1\right)=0\)
đề là vầy hay là vầy vậy bạn ?
\(\dfrac{1}{3x}+\dfrac{2}{5\left(x-1\right)}=0\)
\(\dfrac{1}{3}x+\dfrac{2}{5}\left(x-1\right)=0\)
\(=\dfrac{1}{3}x+\dfrac{2}{5}x-\dfrac{2}{5}+0\)
\(=\dfrac{11}{15}x=\dfrac{2}{5}\)
\(x=\dfrac{2}{5}:\dfrac{11}{15}\)
\(x=\dfrac{2}{5}.\dfrac{15}{11}\)
\(x=\dfrac{6}{11}\)
Vậy x = \(\dfrac{6}{11}\)